DQPSK modulation and demodulation using SAW device. Issue 17 (20th November 2017) - Roy, Arijit; Nemade, Harshal B.; Bhattacharjee, Ratnajit; Kushwah, Vinod
Abstract : A Differential quadrature phase shift keying (DQPSK) modulator and demodulator system incorporating surface acoustic wave (SAW) device is presented. The SAW device in the modulator consists of four delay lines corresponding to different phase delays and generates phase shift keyed radio‐frequency signals. In the demodulator section, another SAW device performs addition operation between two consecutive received signals to obtain the phase difference. The DQPSK demodulation is extended for the demodulation of quadrature phase shift keying signal without the requirement of locally generated reference carrier. The operation of the proposed DQPSK system using SAW along with the bit error rate (BER) performance is presented. The effect of additional phase delay in the received signal on BER is also presented. Addition operation of the received signals using SAW is also verified using simulation.